Unveiling the wealth-bone connection: How socioeconomic status influences trabecular bone health - Yuan Zhang; Tingxiao Zhao; Yanlei Li; Kai Chen; Qice Sun (PLoS ONE, 2025)
Background Currently, the relationship between socioeconomic status (SES) and trabecular bone score (TBS) remains unclear. This study uses existing data from the National Health and Nutrition Examination Survey (NHANES) to test the hypothesis that SES, measured by the poverty income ratio (PIR), is associated with TBS among adults in the United States of America. Methods This study analyzed the relationship between SES and TBS in 7,832 adults using data from the 2005–2008 NHANES. The TBS data were obtained from pre-existing lumbar spine DXA scans collected in the NHANES database. The study employed a multivariable linear regression model, adjusting for various confounding factors, to examine the association between the PIR and TBS. Additionally, demographic characteristics were described, stratified analyses, single factor analysis, smooth curve fitting, and interaction analysis were conducted. Results Results showed that PIR was positively correlated with TBS (β = 0.0019, 95% CI 0.0002–0.0035, P < 0.05), and high-income individuals had a TBS 0.018 higher than low-income individuals (95% CI 0.0106–0.0254, P < 0.001). Smooth curve fitting analysis revealed a linear relationship between PIR and TBS. Stratified analysis showed that this positive correlation was particularly evident among adults aged 50 and older, observed specifically in Mexican Americans and individuals of European and African ancestry. Conclusions Our research shows that there is a significant positive correlation between adult SES and TBS. Higher household income levels correspond to better TBS levels, which can help prevent osteoporosis and fractures. When developing strategies for the prevention and treatment of osteoporosis, healthcare professionals and policymakers should consider the impact of socioeconomic inequalities.